What Makes Decentralisation in Developing Countries Pro-poor? - Johannes Jtting ; Elena Corsi ; Cline Kauffmann; Ida Mcdonnell; Holger Osterrieder Nicolas Pinaud ; Lucia Wegne (The European Journal of Development Research, Vol.17, No.4, December 2005, 2005)
Decentralisation has been advocated by donors and development agencies as an instrument to ensure broader participation of citizens as well as to improve local governance leading to poverty reduction from the bottom up. On the basis of a comprehensive review of nine case studies documented in the literature, this study questions this assumption. According to our findings, a clear link between decentralisation and a reduction in poverty cannot be established. Two important policy lessons emerge from this study. First, in an environment where the central state barely fulfils basic functions and is not interested in giving power and resources to local tiers of government, decentralisation should not be a priority for donors as it could be rather counter-productive. Second, in countries that fulfil basic prerequisites, decentralisation could be a powerful tool for poverty reduction.